The Role of Technology in Addressing the Education Gap in Indonesia's Remote Areas - Firayani (EduTech Journal, 2024)
This study examines the impact of culture-based pedagogy on student engagement in classrooms in Southeast Asia, focusing on how the integration of local cultural elements into the curriculum affects student participation and motivation. A qualitative approach was used through case studies in Indonesia, Thailand, and Malaysia. Data were collected through teacher and student interviews, classroom observations, and analysis of curriculum documents. Data were analyzed using thematic analysis techniques to identify key patterns related to the impact of culture-based pedagogy. Findings indicate that culture-based pedagogy significantly increases student engagement. Integration of local culture into learning increases student participation, motivation to learn, and comprehension of the material. In Thailand and Malaysia, students showed greater interest and engagement in classroom activities when local cultural elements were implemented. Despite the benefits, challenges such as limited teacher training, lack of culture-based teaching materials, and differences in educational resources remain barriers to the implementation of this pedagogy. To maximize the effectiveness of culture-based pedagogy, better teacher training, development of culturally relevant teaching materials, and support for educational infrastructure are needed. Education policies should support the integration of local culture to improve overall student engagement.